2003
DOI: 10.1097/01.mco.0000078983.18774.cc
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in the pathogenesis of cancer cachexia

Abstract: Although the search for the cachectic factor(s) started a long time ago, and although many scientific and economic efforts have been devoted to its discovery, we are still a long way from knowing the whole truth. A lot of progress has been made, however, in understanding the role of different cytokines - tumor necrosis factor and IL-6 in particular - in muscle wasting associated with cancer cachexia, perhaps the most paradigmatic feature of this complex syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
83
1
15

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(99 citation statements)
references
References 39 publications
0
83
1
15
Order By: Relevance
“…Both IL-6 and TNF-a levels were increased significantly in the TB group, which confirmed the role of TNF-a besides IL-6, in the pathogenesis of cancer cachexia in the C26 model. By contrast, levels of IL-4, in literature stated as an anti-cachectic cytokine (Argiles et al, 2003), showed a significant decrease in the TB group, which is in agreement with the cachectic state of the animals.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…Both IL-6 and TNF-a levels were increased significantly in the TB group, which confirmed the role of TNF-a besides IL-6, in the pathogenesis of cancer cachexia in the C26 model. By contrast, levels of IL-4, in literature stated as an anti-cachectic cytokine (Argiles et al, 2003), showed a significant decrease in the TB group, which is in agreement with the cachectic state of the animals.…”
Section: Discussioncontrasting
confidence: 38%
“…In experiment B, the pro-inflammatory cytokines IL-6 and TNF-a were measured. These cytokines have been described as procachectic cytokines involved in different metabolic changes associated with wasting during cancer cachexia (Toomey et al, 1995;Argiles et al, 2003;Argiles, 2005). In literature, TNF-a levels measured in the C26 model were below the detection limit (Strassmann et al, 1992a;Soda et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In studies of rodents, injection of TNF-α and IL-1 initially reduces food intake. However, tolerance soon develops after repetitive administration of TNF-α [35]. The relation between plasma C3 and weight gain could hypothetically reflect the effects of these cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…[9,10] As a consequence of the acute-phase response, degradation of skeletal muscle proteins occurs, causing muscle atrophy. [16] The acute-phase response has been associated with hyper-metabolism and tissue catabolism, [21,22] and some acute-phase proteins such as C-reactive protein (CRP) have been shown to play a role in modulating the immune response and in predicting adverse outcomes in cancer patients. [5] CRP has been shown to be a strong marker of systemic inflammation in cancer patients and has been associated with the presence of anorexia, hyper-metabolism, accelerated weight loss, and shortened survival.…”
Section: Introductionmentioning
confidence: 99%